Resistant hyponatraemia in a patient with follicular lymphoma and heart failure with reduced ejection fraction: a case report. Issue 5 (15th May 2021) - Butler, Jennifer; Miro, Firas; Al-Mohammad, Abdallah
Abstract: Background: Hyponatraemia is a common problem in patients with heart failure. It can be difficult to treat, especially in the presence of the patient's needs for diuresis and manipulation of the renin–angiotensin–aldosterone system (RAAS). Case summary: This concerns a 74-year-old woman with follicular lymphoma and severe global left ventricular systolic dysfunction secondary to treatment with R-CHOP chemotherapy. She presented a difficult challenge in the management of her decompensated heart failure alongside hyponatraemia as low as 113 mmol/L. This was resistant to standard treatment. The resistance to usual measures necessitated treatment with Tolvaptan, a selective arginine vasopressin V2 inhibitor used to treat hyponatraemia in syndrome of inappropriate anti-diuretic hormone. This, along with a strict fluid restriction of 500 mL/day, resolved the patient's hyponatraemia and enabled her discharge home on tolerated heart failure treatment. She has now remained stable for almost 12 months. Discussion: The potential causes of hyponatraemia are discussed along with the role of Tolvaptan in its management.